The Influence of Employer Branding and E-Recruitment on Job Interest of Gen Z at SMK Negeri 1 Katapang - Muhammad Faisal Malik; Didip Diandra (Journal of Social Research, 2026)
Companies need to understand that there is a phenomenon of shifting trends in job applications, especially in young job applicants such as generation Z. This study aims to analyze the influence of employer branding and E-Recruitment for the work interests of generation Z at SMK Negeri 1 Katapang. This study uses quantitative descriptive methods and sampling techniques, namely purposive sampling. The sample used in this study was 240 respondents of grade 12 students and students at SMK Negeri 1 Katapang which were collected through Google form. Data analysis tools using Partial Least Square (PLS) with Software PLS version 4.0.0. The results of the study show that there is a positive and significant relationship in the first hypothesis. After that, the study also found that E-recruitment had a positive and significant effect on the interest of generation z to apply for jobs at SMK Negeri 1 Katapang.